Nurturing Student Leadership from Within: An Integrative Framework of School Culture Management and 'The Leader in Me' - Renisa Septia; Lina Novita; Elly Sukmanasa (JURNAL AL-TANZIM, 2026)
This study aims to analyze how school culture management strengthens student leadership by integrating The Leader in Me approach and student voice from an educational management perspective. This research uses a qualitative approach with a case study design conducted in a school. Data were collected through in-depth interviews, passive participant observation, and document analysis. Data analysis was conducted using the Miles and Huberman interactive model, while data validity was tested through source and technique triangulation. The results show that student leadership develops through an integrated school culture management system, rather than through a stand-alone leadership program. The core values of ICARE (Integrity, Collaboration, Active, Respect, and Excellence) serve as the foundation of school culture in building and strengthening student leadership. These values are internalized through a continuous process of learning, role modeling, and habituation within the framework of The Leader in Me approach. Furthermore, the internalization of these values is achieved through the Kreativa Voice of Leaders program, which provides a space for student participation to convey ideas, develop self-leadership, and strengthen social leadership. Based on these findings, this study proposes an integrative framework to strengthen student leadership through school culture management. This framework provides practical implications for educational management in developing sustainable student leadership through strengthening values, culture, and active student participation.